Continued fractions and cryptographic applications - Sookraj, Priyanka (My University, 2022)
In this dissertation, Michael J. Wiener’s proposed attack on short secret exponents used in the RSA cryptosystem is studied and thus an application of continued fractions in the cryptanalysis is highlighted. Furthermore, some variants and improvements to the attack proposed by A. Dujella, M. Bunder and J. Tonien are studied.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Mathematics to the Faculty of Science, University of the Witwatersrand, Johannesburg, 2022
Keywords: Continued Fractions; Cryptographic Applications